2015
DOI: 10.1016/j.surg.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative quality as well as quantity of skeletal muscle on survival after resection of pancreatic cancer

Abstract: Preoperative sarcopenia, indicating low quality and quantity of skeletal muscle, is closely related to mortality after resection of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
233
5
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(250 citation statements)
references
References 26 publications
10
233
5
2
Order By: Relevance
“…Although in some studies a correlation between PA and post‐operative complications was seen, the majority have failed to prove a relationship between PA‐assessed sarcopenia and survival 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23. Only few have actually assessed the agreement between PA and SMA within their population; Jones et al studied 100 patients with colorectal cancer and reported a Spearman correlation of 0.8 for PA and SMA and a Spearman correlation of 0.94 for PA and PLW, which could not be reproduced in our cohort 11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in some studies a correlation between PA and post‐operative complications was seen, the majority have failed to prove a relationship between PA‐assessed sarcopenia and survival 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23. Only few have actually assessed the agreement between PA and SMA within their population; Jones et al studied 100 patients with colorectal cancer and reported a Spearman correlation of 0.8 for PA and SMA and a Spearman correlation of 0.94 for PA and PLW, which could not be reproduced in our cohort 11.…”
Section: Discussionmentioning
confidence: 99%
“…PA has shown a correlation with post‐operative complications in individual studies on colorectal cancer, colorectal liver metastases, kidney cancer, bladder cancer, cholangiocarcinoma, and hepatocellular cancer,11, 12, 13, 14, 15, 16 while this effect was not seen in other pancreatic cancer, endometrial cancer, biliary cancer, or sarcoma studies 17, 18, 19, 20. Interestingly, only few cancer studies were able to show a correlation between PA and survival 21, 22, 23. In a small number of non‐cancer studies, decreased psoas muscle area has also been correlated with higher rates of morbidity24, 25, 26 and mortality25, 27, 28, 29 in patients undergoing cardiothoracic, gastro‐intestinal, and spinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional areas (cm 2 ) of these muscles were measured by manual tracing on the CT images, and their sum was calculated. These sums were normalized for each patient to provide a psoas muscle index value (PMI; cm 2 /m 2 ) (33,34). The median PMI value was calculated for males and females separately.…”
Section: Patients and Indications For Systemic Chemotherapymentioning
confidence: 99%
“…PC was diagnosed primarily based on the current guidelines (35). Briefly, abdominal US and dynamic CT of the pancreas was routinely performed prior to initiating systemic chemotherapy (33). In cases with atypical radiological findings for PC, tumor biopsy or EUS-guided fine needle aspiration was considered (36).…”
Section: Patients and Indications For Systemic Chemotherapymentioning
confidence: 99%
“…In addition to LT, we recently reported the significance of preoperative low quality as well as quantity of skeletal muscle in patients who underwent surgery for hepatocellular carcinoma, intrahepatic cholangiocarcinoma, biliary cancer, and pancreatic cancer (12)(13)(14)(15). In these cancers, low skeletal muscle mass and muscle quality are closely involved with impaired outcomes.…”
Section: To the Editormentioning
confidence: 99%